Tendenser i nutidig fransk poesi - Litteralisme og litterær dj’ing som postpoetiske strategier - Marcussen, Louise Højgaard (Passage - Tidsskrift for litteratur og kritik, 2012)
Louise Højgaard Marcussen: “Trends in Contemporary French Poetry. Literalism and Literary DJ’ing as Post-poetic Strategies” The article describes the post-poetic impulse in contemporary French literature. Taking the essay Sorties by Jean-Marie Gleize as vantage point, Marcussen investigates two different ways of breaking off from the essentialist poetic tradition: on the one hand a strand of poetry aiming at critical resistance towards the tradition, exemplified by a reading of Christophe Tarkos’ “Le Bol”; and on the other hand writers trying to activate tradition in new forms, exemplified through a reading of Franck Leibovici’s portraits chinois.